Estudio de la génesis de la veta azul basado en un control geológico estructural en las labores mineras circunscritas de la concesión “Nueva Esperanza 4” código 300086, ubicado en la parroquia Zaruma y Sinsao del cantón Zaruma, provincia de El Oro. - Ordóñez Tapia, Luis Andres (2019)
The "STUDY OF THE BLUE VET GENESIS BASED ON A STRUCTURAL GEOLOGICAL CONTROL IN THE CIRCUNSCRITER MINING WORKS OF THE CONCESSION" NEW HOPE 4 "CODE 300086, LOCATED IN THE ZARUMA PARISH AND SINSAO DEL CANTÓN ZARUMA, PROVINCE OF EL ORO", elaborated by means of a diagnosis of the bibliographic information of the mining district Zaruma-Portovelo and field information raised from the mining works in the concession "NUEVA ESPERANZA 4" to the northeast of Zaruma, the results will be useful for the exploration of areas enriched in precious metals. Mineralogical analysis, gold content assays, mapping of lithological units and structural diagnosis allowed us to relate the mineralization of the site, to a transition zone between a polymetallic phase to an epithermal phase enriched in precious metals, located east of the concession. You can also notice the presence of mineral bodies with a crustiform and breached texture; with presence of calcite, adularia and carbonates evidenced in these mining galleries; Attributing to a Hot Spring boiling process. The lithology is dominated by andesites, porphyry andesites, basaltic andesites and some gaps related to the Muluncay member, mainly the mineralization is hosted by andesites of the member Portovelo. Structures with courses NE-SW and NW-SE control the mineralization with dextral and sinestral movements, characteristic of faults R and R'that together with the major faults are concordant to the kinematics proposed in the Riedel model. The described mineralogy was grouped in three stays plus a stage of supérgeno enrichment, some recrystallization textures are recognizable for epithermal quartz, additionally chemical analysis for detection of silver and gold maintain 92/1 relationships in samples of the Blue vein. Key Words: Zaruma, Epithermal, Intermediate sulfurization, stays, genesis